Penal Protection of the Islamic Rituals in the Algerian Legislation - Djamal, Soliman (Journal of Legal Studies and Researches, 2024)
The objective of this study is to know that Islamic rituals are protected by the Algerian criminal law from any assault. The results obtained are that the Algerian legislator guaranteed criminal protection against crimes. Mocking the known religion, violating the sanctity of cemeteries, the crime of desecrating the Holy Qur’an, and, as a general rule, every mockery of one of the rituals of Islam.